Assessing Student Progress toward the Equipped for the Future Standards: Issues and Lessons to Date - Brenda Bell; Peggy McGuire (Adult Education Research Conference, 2000)
Equipped for the Future (EFF), the national standards-based system reform initiative for adult education, has developed sixteen content standards that define the core knowledge and skills adults need to effectively carry out their primary roles. The current stage of EFF research is focused on development of performance standards for these content standards. This roundtable will discuss issues and findings from this field-based research.